Petanque Sports Profile in Sumenep Regency - Firdauz, Noer Wachid Riqzal; Weldani, Feri; Basri, Moh. Hasan (Universitas Majalengka, 2024)
This research is qualitative research with primary and secondary data collection. The data collection techniques in this research are observation, interviews and documentation, while the analysis techniques are data reduction, data presentation and verification. The object of this research is the sport of Petanque in Sumenep Regency, which specifically discusses the profile and history of Petanque in Sumenp Regency. This research aims to determine the profile and history of Petanque in Sumenep Regency. The results of this research are that Petanque entered Sumenep Regency in 2019, brought by Feri Weldani and Noer Wachid Riqzal Firdaus, then officially established on November 6 2020. Even though it is considered a new sport, there have been many achievements at both levels to date. Regency, Provincial and National, and Petanque in Sumenep Regency already have complete organizational equipment, both personnel and institutional. Apart from that, the facilities and infrastructure owned for the development of petanque are eight sets of Chinese Bosi, 13 sets of French Bosi, five field lines, 15 Circles and 10 Boka.